Retrospective analysis of amantadine response and predictive factors in intensive care unit patients with non-traumatic disorders of consciousness - Corinna Blum; Constanze Single; Kornelia Laichinger; Anna Hofmann; Tim W. Rattay; Tim W. Rattay; Kamaldeen Adeyemi; Reimer Riessen; Michael Haap; Helene Häberle; Ulf Ziemann; Annerose Mengel; et al. (Frontiers in Neurology)
BackgroundDisorders of consciousness (DoC) in non-traumatic ICU-patients are often treated with amantadine, although evidence supporting its efficacy is limited.MethodsThis retrospective study analyzed non-traumatic DoC-patients treated with amantadine between January 2016 and June 2021. Data on patient demographics, clinical characteristics, treatment specifications, and outcomes were extracted from electronic medical records. Patients were classified as responders if their Glasgow Coma Scale (GCS) improved by ≥3 points within 5 days. Good outcome was defined as a modified Rankin Scale (mRS) of 0–2. Machine learning techniques were used to predict response to treatment.ResultsOf 442 patients (mean age 73.2 ± 10.7 years, 41.0% female), 267 (60.4%) were responders. Baseline characteristics were similar between groups, except that responders had lower baseline GCS (7 [IQR 5–9] vs. 8 [IQR 5–10], p = 0.030), better premorbid mRS (2 [IQR 1–2] vs. 2 [IQR 1–3], p < 0.001) and fewer pathological cerebral imaging findings (45.7% vs. 61.1%, OR 0.56, 95% CI: 0.36–0.86, p = 0.008). Responders exhibited significantly lower mortality at discharge (13.5% vs. 27.4%, OR 0.41, 95% CI: 0.25–0.67, p < 0.001) and follow-up (16.9% vs. 32.0%, OR 0.43, 95% CI: 0.24–0.77, p = 0.002). Good outcomes were more frequent in responders at follow-up (4.9% vs. 1.1%, OR 6.14, 95% CI: 1.35–28.01, p = 0.004). In multivariate analysis higher premorbid mRS (OR 0.719, 95% CI 0.590–0.875, p < 0.001), pathological imaging results (OR 0.546, 95% CI 0.342–0.871, p = 0.011), and experiencing cardiac arrest (OR 0.542, 95% CI 0.307–0.954, p = 0.034) were associated with lower odds of response. Machine learning identified key predictors of response, with the Stacking Classifier achieving the highest performance (accuracy 64.5%, precision 66.6%, recall 64.5%, F1 score 61.3%).ConclusionThis study supports the potential benefits of intravenous amantadine in non-traumatic DOC-patients. Higher premorbid mRS, and pathological cerebral imaging were key predictors of non-response, offering potential avenues for patient selection and treatment customization. Findings from this study informed the design of our ongoing prospective study, which aims to further evaluate the long-term efficacy of amantadine.